Transforming growth factor beta induces the production of interleukin 6 by human peripheral blood mononuclear cells. - Turner, M; Chantry, D; Feldmann, M (1990)
Previous studies have indicated that the cytokine transforming growth factor beta 1 (TGF beta 1) has immunosuppressive properties and can inhibit the production of tumor necrosis factor (TNF) and Interleukin 1 (IL 1) by human peripheral blood mononuclear cells. In this study, we have examined the effects of TGF beta 1 on the production of Interleukin 6 (IL 6) by human peripheral blood mononuclear cells. Treatment with only TGF beta 1 leads to the induction of IL 6, and this was both dose- and time-dependent. The effect of TGF beta 1 was evident at the level of IL 6 mRNA, suggesting TGF beta 1-induced de novo synthesis of IL 6. Induction of IL 6 by TGF beta 1 was specific, as other cytokines made by mononuclear cells (TNF and IL 1) were not induced by TGF beta 1. Furthermore, when a panel of stimuli were compared for their ability to induce IL 1, TNF and IL 6 in the presence or absence of TGF beta 1, IL 6 levels were augmented in the presence of TGF beta 1, while the induction of IL 1 and TNF was inhibited significantly. These results indicate that TGF beta 1 has complex effects on the production of cytokines by peripheral blood mononuclear cells and that TGF beta 1 is not inhibitory for all cytokine production. The ability of TGF beta 1 to induce IL 6 suggests that IL 6 may mediate some of the effects of TGF beta 1.